Factors Affecting Social Studies Learning Achievement: A Comparative Study on Grade IX Students of SMP Negeri 1 Bandar Lampung - Rusman, Tedi; Putri, Rahmah Dianti; Hestiningtyas, Widya; Ramadan, Figo Muhammad; Azzahroh, Faridatun (Economic Education and Entrepreneurship Journal, 2024)
Learning outcomes serve as a reflection of the success of achieving the objectives of the learning process. These outcomes are influenced by various factors, including internal factors, such as students' physical and psychological conditions, and external factors, such as family, school, and community environments. This study aims to analyze the impact of these factors on the learning outcomes of Grade IX students in social studies at SMP Negeri 1 Bandar Lampung. Using a quantitative correlational method, the study collected data through questionnaires with a Likert-scale format and applied percentage-based analysis techniques. The findings indicate significant relationships between the identified factors and students' learning outcomes, emphasizing the interconnectedness of internal and external influences. This research highlights the need for collaborative efforts among teachers, parents, and the community to create a supportive environment that fosters better learning outcomes in social studies.DOI: http://dx.doi.org/10.23960/E3J/v7.i2.235-240